2019
DOI: 10.3748/wjg.v25.i29.4019
|View full text |Cite
|
Sign up to set email alerts
|

Post-endoscopic retrograde cholangiopancreatography pancreatitis: A systematic review for prevention and treatment

Abstract: BACKGROUND Post endoscopic retrograde cholangiopancreatography (ERCP) is comparatively complex application. Researchers has been investigated prevention of post-ERCP pancreatitis (PEP), since it has been considered to be the most common complication of ERCP. Although ERCP can lead various complications, it can also be avoided. AIMS To study the published evidence and systematically review the literature on the prevention and treatment for PEP. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 154 publications
(183 reference statements)
1
39
0
10
Order By: Relevance
“…It has been suggested that other risk factors may increase the risk of post-ERCP pancreatitis synergistically. For instance, Sphincter of Oddi dysfunction, an independent risk factor for the development of post-ERCP pancreatitis, is more common in women overall, which could make the actual association between women and post-ERCP pancreatitis difficult to distinguish [ 56 ]. Furthermore, Freeman et al found the highest risk of post-ERCP pancreatitis (42%) in female patients with normal serum bilirubin, Sphincter of Oddi dysfunction, and difficult biliary cannulation [ 50 ].…”
Section: Sex Differences In Pancreatitismentioning
confidence: 99%
“…It has been suggested that other risk factors may increase the risk of post-ERCP pancreatitis synergistically. For instance, Sphincter of Oddi dysfunction, an independent risk factor for the development of post-ERCP pancreatitis, is more common in women overall, which could make the actual association between women and post-ERCP pancreatitis difficult to distinguish [ 56 ]. Furthermore, Freeman et al found the highest risk of post-ERCP pancreatitis (42%) in female patients with normal serum bilirubin, Sphincter of Oddi dysfunction, and difficult biliary cannulation [ 50 ].…”
Section: Sex Differences In Pancreatitismentioning
confidence: 99%
“…[2][3][4][5][6] Consequently, multiple pharmacological and procedural interventions have been used by endoscopists to reduce the risk of PEP over the last few decades. [7][8][9][10][11] These include but are not limited to administration of rectal NSAIDs, infusion of lactated ringers, use of topical epinephrine, placement of pancreatic duct stents and use of guidewire cannulation.…”
Section: Temporal Trends and Mortality Of Post-endoscopic Retrograde mentioning
confidence: 99%
“…The rate of pancreatitis varies widely in the literature but is around 5% with the vast majority being mild, and instances of severe pancreatitis range between 0.1 and 0.5%. 18,19 Other complications of ERCP include infection, intestinal perforation, and hemorrhage if a sphincterotomy is performed.…”
Section: Complicationsmentioning
confidence: 99%